Indonesian dentists knowledge, attitudes and practices in COVID-19 pandemic - Suwargiani, Anne Agustina; Arief, Erry Mochamad; Setiawan, Asty Samiaty; Putri, Fidya Meditia; Hamdani, Ardena Maulidia; Sanjaya, Azlina Nuur; Yubiliani, Gilang; Susilawati, Sri; Aripin, Dudi; Djuastina, Nina; Widyaputra, Sunardhi (Faculty of Dentistry Universitas Padjadjaran, 2022)
ABSTRACTIntroduction: Dentists play a significant role in preventing the transmission of 2019-nCoV. Recommended infection control measures during dental practice can block the route of person-to-person transmission. Dentists and their personnel are used to assess the risk of cross-infection. This study aimed to obtain dentists' knowledge, attitudes, and practices regarding the Covid-19 pandemic in Indonesia. Methods: A cross-sectional study was conducted on a sample of licensed dentists using the convenience sampling technique. The minimum sample size was counted using the formula for a descriptive analysis of one group with the expected proportion of 50% and the confidence level of 95%, and obtained 407 respondents from 31 provinces. Data was collected using a questionnaire distributed via a shortened link. 99.75% of respondents knew personal protective equipment, but only 84.28% knew the proper removal procedure. 99.75% of respondents knew about dental devices that cause aerosols, and all respondents knew about social and physical distancing. Result: Dentists’ attitudes regarding personal protective equipment were that they needed and maintained it during the pandemic. All respondents stated that social and physical distancing was critical and must be maintained while providing health services. Regarding their practices, all respondents did social and physical distancing in their daily lives and during dental procedures. Conclusion: Dentists' knowledge is already good in several ways, but with several matters that still need to be improved, their attitudes and practices are good criteria. Keywords: smart Odontogram; medical record; application; usability testing; user’s experience